Vlachs and Cumans in Bulgarian service under the Asen dynasty - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2007)
The article highlights the circumstances surrounding the presence of Vlachs and Cumans in the Bulgarian army between 1186 and 1241. The background to these considerations is the complex political relations between Bulgaria and Byzantium and the establishment of the Latin Empire, which served to strengthen Bulgarian-nomadic alliances. The aims of the text are to show the importance of Bulgaria's military and political ties with nomadic tribes and to highlight their role in the military campaigns conducted by Bulgarian tsars. Particular attention is paid to analysing the chronology of contacts, their nature and consequences for the stability of the Bulgarian state. A critical analysis of Byzantine, Latin and Bulgarian sources was used. The conclusions indicate that the participation of nomads was of fundamental importance for Bulgaria: their mobile cavalry facilitated military operations, especially in the fight against the Latins, and dynastic marriages helped to maintain alliances. At the same time, dependence on auxiliary troops exposed the weakness of Bulgaria's own forces and exposed the state to the whims of its allies. Bulgaria's cooperation with nomads was ambivalent – it was both a strengthening and destabilising factor for the state.